2015
DOI: 10.18203/2394-6040.ijcmph20150284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of implementation of 5S Campaign in urban health center run by municipal corporation, Gujarat, India

Abstract: Background: Despite significant progress in improvement of Government health care delivery system over past decade, community is reluctant to accept it because of substandard level of quality. "5S" is one of the strategies used to improve the physical quality and work efficiency of organization. 5S stands for five Japanese words which can be translated in English as Sort, Set in order, Shine, Standardize, and Sustain. Rajkot Municipal Corporation has adopted 5S strategy within its health centers with the aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Our review identified service areas and geographical locations involved in the empirical 5S application. 5S was applied to primary health-care facilities [ 28 , 33 , 34 ] and different locations or sectors of hospitals, including a pharmacy [ 24 ]; an emergency department [ 25 ]; an operating room [ 26 ]; multiple departments (central supply, histology laboratory, ICU, medical-surgical inpatient care unit, and infusion center) of several hospitals [ 27 ]; a laboratory [ 29 ]; a surgical clinic [ 31 ]; multiple locations of hospitals (or without specific information about target locations) [ 32 , 35 – 38 ]; and central warehouses [ 30 ]. Of the 15 studies, six were conducted in the USA [ 26 , 27 , 29 31 ], one in the UK [ 35 ], and eight in low- and middle-income countries, namely Brazil, India, Jordan, Senegal, Sri Lanka, and Tanzania [ 24 , 25 , 28 , 32 – 34 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review identified service areas and geographical locations involved in the empirical 5S application. 5S was applied to primary health-care facilities [ 28 , 33 , 34 ] and different locations or sectors of hospitals, including a pharmacy [ 24 ]; an emergency department [ 25 ]; an operating room [ 26 ]; multiple departments (central supply, histology laboratory, ICU, medical-surgical inpatient care unit, and infusion center) of several hospitals [ 27 ]; a laboratory [ 29 ]; a surgical clinic [ 31 ]; multiple locations of hospitals (or without specific information about target locations) [ 32 , 35 – 38 ]; and central warehouses [ 30 ]. Of the 15 studies, six were conducted in the USA [ 26 , 27 , 29 31 ], one in the UK [ 35 ], and eight in low- and middle-income countries, namely Brazil, India, Jordan, Senegal, Sri Lanka, and Tanzania [ 24 , 25 , 28 , 32 – 34 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the studies, 5S was combined with other tools and its application was meant for different quality improvement goals. Ten of the 15 empirical studies involved the application of 5S only [ 27 , 28 , 30 , 32 38 ], whereas the other five studies combined several tools and methods including 5S [ 24 26 , 29 , 31 ]. In addition, 5S was regarded as a method under the framework of lean health-care by authors in ten studies [ 24 27 , 29 31 , 33 , 35 , 36 ] and toward better quality management (or total quality management (TQM)) in three studies [ 32 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the faculty member responded that "SOPs for equipment and analyte estimation has improved the internal as well as external quality checks." Many studies in the past have pointed out the benefits of organised and safe workplace after implementing 5S (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Sustain: To train people to practice the 5S system continuously, so that it becomes habitual and ingrained in the culture of the organisation. 3 5S is considered to be the building block or the foundation upon which lean healthcare rests. It is also defined as the process that provides the foundation for building a lean healthcare environment.…”
Section: Set In Ordermentioning
confidence: 99%